The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1103/physreva.81.022323
|View full text |Cite
|
Sign up to set email alerts
|

Quantum stochastic walks: A generalization of classical random walks and quantum walks

Abstract: We introduce the quantum stochastic walk (QSW), which determines the evolution of generalized quantum mechanical walk on a graph that obeys a quantum stochastic equation of motion. Using an axiomatic approach, we specify the rules for all possible quantum, classical and quantum-stochastic transitions from a vertex as defined by its connectivity. We show how the family of possible QSWs encompasses both the classical random walk (CRW) and the quantum walk (QW) as special cases, but also includes more general pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
176
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 35 publications
2
176
0
Order By: Relevance
“…Nevertheless there are many other mechanism of decoherence, see for example [31]. To our knowledge this pioneer problem was well posed in van Kampen's paper [12], but many other related approaches have also been presented in the literature [15,40]. The propagation of photons in waveguide lattices have been studied in recent years [24,25], and they are possible scenarios where our present results can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless there are many other mechanism of decoherence, see for example [31]. To our knowledge this pioneer problem was well posed in van Kampen's paper [12], but many other related approaches have also been presented in the literature [15,40]. The propagation of photons in waveguide lattices have been studied in recent years [24,25], and they are possible scenarios where our present results can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…If only the coherent term was present the QSW would correspond to a standard CTQW. On the other hand, it can be shown that if only the incoherent term was present the QSW would correspond to a classical random walk for the diagonal elements of ρ(t) [22]. A standard stochastic method to study the dynamics described by eq.…”
Section: Quantum Stochastic Walksmentioning
confidence: 99%
“…QSWs are a class of stochastic processes introduced in [22] with the purpose of generalizing both continuous time quantum walks, and classical random walks [29] into a single framework. A QSW is specified by a quantum master equation in Lindblad form [30] describing the evolution of the system's density matriẋ…”
Section: Quantum Stochastic Walksmentioning
confidence: 99%
See 2 more Smart Citations